A Wideband Hybrid Fractal Ring Antenna for WLAN Applications - Atif Jamil; Muhammad Rauf; Abdul Sami; Arsalan Ansari; Muhammad Dawood Idrees (International Journal of Antennas and Propagation)
We propose the design of a novel fractal antenna that is both unique and performance-driven. Two important antenna design features, miniaturization and wideband operation, are combined in this work. A ring-shaped antenna is designed using the well-known fractal geometry. This hybrid geometry is a fusion of meander and Koch curve shapes. The geometrical construction of the proposed antenna is compared to the standard Koch curve geometry. It is shown that combining the meander and Koch curve shapes increases the effective electrical length. The wider bandwidth is achieved by bringing the higher modes together. The overall dimensions of proposed meander Koch curve fractal ring antenna are 45 × 25 × 1.6 mm3. The resonance frequency of the antenna is between 4.94 and 6.12 GHz (% BW = 21.83), which covers the entire 5 GHz WLAN band. The prototype has been fabricated and experimentally verified.